Putative Concussion Biomarkers Identified in Adolescent Male Athletes Using Targeted Plasma Proteomics - Miller, Michael R.; Robinson, Michael; Fischer, Lisa; DiBattista, Alicia; Patel, Maitray A.; Daley, Mark; Bartha, Robert; Dekaban, Gregory A.; Menon, Ravi S.; Shoemaker, J. Kevin; Diamandis, Eleftherios P.; Prassas, Ioannis; et al. (Frontiers in Neurology, 2021)
Sport concussions can be difficult to diagnose and if missed, they can expose athletes to greater injury risk and long‐lasting neurological disabilities. Discovery of objective biomarkers to aid concussion diagnosis is critical to protecting athlete brain health. To this end, we performed targeted proteomics on plasma obtained from adolescent athletes suffering a sports concussion. A total of 11 concussed male athletes were enrolled at our academic Sport Medicine Concussion Clinic, as well as 24 sex‐, age‐ and activity‐matched healthy control subjects. Clinical evaluation was performed and blood was drawn within 72 hours of injury. Proximity extension assays were performed for 1,472 plasma proteins; a total of 6 proteins were considered significantly different between cohorts (P<0.01; 5 proteins decreased and 1 protein increased). Receiver operating characteristic (ROC) curves on the 6 individual protein biomarkers identified had areas‐under‐the curves (AUCs) for concussion diagnosis ≥0.78; antioxidant 1 copper chaperone (ATOX1; AUC 0.81, P<0.003), secreted protein acidic and rich in cysteine (SPARC; AUC 0.81, P=0.004), cluster of differentiation 34 (CD34; AUC 0.79, P=0.006), polyglutamine binding protein 1 (PQBP1; AUC 0.78, P=0.008), insulin-like growth factor-binding protein-like 1 (IGFBPL1; AUC 0.78, P=0.008) and cytosolic 5'-nucleotidase 3A (NT5C3A; AUC 0.78, P=0.009). Combining 3 of the protein biomarkers (ATOX1, SPARC and NT5C3A), produced an AUC of 0.98 for concussion diagnoses (P<0.001; 95% CI: 0.95, 1.00). Despite a paucity of studies on these 3 identified proteins, the available evidence points to their roles in modulating tissue inflammation and regulating integrity of the cerebral microvasculature. Taken together, our exploratory data suggest that 3 or less novel proteins, which are amenable to a point-of-care immunoassay, may be future candidate biomarkers for screening adolescent sport concussion. Validation with protein assays is required in larger cohorts.